2021
DOI: 10.3390/antibiotics10121502
|View full text |Cite
|
Sign up to set email alerts
|

Efflux Pump Mediated Antimicrobial Resistance by Staphylococci in Health-Related Environments: Challenges and the Quest for Inhibition

Abstract: The increasing emergence of antimicrobial resistance in staphylococcal bacteria is a major health threat worldwide due to significant morbidity and mortality resulting from their associated hospital- or community-acquired infections. Dramatic decrease in the discovery of new antibiotics from the pharmaceutical industry coupled with increased use of sanitisers and disinfectants due to the ongoing COVID-19 pandemic can further aggravate the problem of antimicrobial resistance. Staphylococci utilise multiple mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 305 publications
(346 reference statements)
1
50
0
Order By: Relevance
“…The advantages of using lipid-based NCs, surface modification methods to enhance the efficiency and stability of phage-loaded liposomes, preparation of multiple nanoemulsions suitable for phage cocktails, phage loaded nanofibers; advanced core shell nanofibers enabling immediate, biphasic and delayed release as well as smart phage release delivery platforms were discussed [ 83 , 84 , 85 , 86 ]. Bacterial resistance is associated with the overexpression of relative activities of the efflux pump and efflux transporters situated in the membrane of bacteria, which has a crucial impact on the inhibition of the intracellular drug intake and suppression of the drug activities [ 87 , 88 ]. However, the effective inhibition of transporter activity can be achieved using NPs as encapsulating agents, enabling enhanced intracellular accumulation of drugs and helping to overcome bacterial resistance.…”
Section: Nanosystems and Their Benefitsmentioning
confidence: 99%
“…The advantages of using lipid-based NCs, surface modification methods to enhance the efficiency and stability of phage-loaded liposomes, preparation of multiple nanoemulsions suitable for phage cocktails, phage loaded nanofibers; advanced core shell nanofibers enabling immediate, biphasic and delayed release as well as smart phage release delivery platforms were discussed [ 83 , 84 , 85 , 86 ]. Bacterial resistance is associated with the overexpression of relative activities of the efflux pump and efflux transporters situated in the membrane of bacteria, which has a crucial impact on the inhibition of the intracellular drug intake and suppression of the drug activities [ 87 , 88 ]. However, the effective inhibition of transporter activity can be achieved using NPs as encapsulating agents, enabling enhanced intracellular accumulation of drugs and helping to overcome bacterial resistance.…”
Section: Nanosystems and Their Benefitsmentioning
confidence: 99%
“…Consequently, methicillin resistant Staphylococcus aureus (MRSA) are prevalent throughout the globe [ 16 ] and they are often resistant to most of the known antibiotics. To this end, different efflux pump inhibitors have been explored as a strategy to overcome antibiotic resistance in S. aureus species [ 17 ]. Recently, our group has shown that IVM has an activity against clinical isolates of S .…”
Section: Introductionmentioning
confidence: 99%
“…The list annotates the Gram-positive pathogen, Staphylococcus aureus, as a high-priority pathogen that causes a wide array of localized or systemic infections, including bacteremia, endocarditis, and implant infections 6 . Drug-resistant strains of Staphylococcus aureus express a diverse set of MFS antiporters in their membranes, including the chromosomally encoded transporters NorA, NorB, and NorC that provide resistance against fluoroquinolones 7 , and QacA and QacB that are plasmid-encoded and are involved in antibacterial efflux 8,9 . QacA is highly prevalent in S.aureus strains resistant to cationic antibacterial compounds, particularly among those associated with nosocomial infections 10 .…”
Section: Introduction Pathogenic Bacteria Gain Antimicrobial Resistan...mentioning
confidence: 99%
“…The MFS transporters involved in drug:proton antiport (DHA) are divided into DHA1 and DHA2 depending on the number of transmembrane (TM) helices (12 or 14, respectively) in each transporter 11 . While transporters like NorA, MdfA, and LmrP comprise 12 TM helices and belong to the DHA1 class of transporters 12-14 , QacA, LfrA, and SmvA comprise 14 TM helices and are part of the DHA2 family 9,15,16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation